2020
DOI: 10.1002/ange.202001854
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalyzed Highly Diastereo‐ and Enantioselective Cyclization–[4+3] Annulation Cascades between 2‐(1‐Alkynyl)‐2‐alken‐1‐ones and Anthranils

Abstract: This work reports gold‐catalyzed [4+3]‐annulations of 2‐(1‐alkynyl)‐2‐alken‐1‐ones with anthranils to yield epoxybenzoazepine products with excellent exo‐diastereoselectivity (dr>25:1). The utility of this new gold catalysis is manifested by applicable substrates over a broad scope. More importantly, the enantioselective versions of these [4+3]‐cycloadditions have been developed satisfactorily with chiral gold catalysts under ambient conditions (DCM, 0 °C); the ee levels range from 88.0–99.9 %. With DFT calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Very recently, Liu and co‐workers disclosed the highly diastereo‐and enantioselective gold‐catalyzed cyclization/[4+3] annulation cascade between 2‐(1‐alkynyl)‐2‐alken‐1‐ones 48 and anthranils 190 to yield epoxybenzoazepine products 191 (Scheme 49). [57] Treatment of species 191 a with Zn powder in DCM at room temperature led to an N−O bond cleavage to deliver benzoazepine derivative 192 in excellent yield without erosion of enantioselectivity.…”
Section: Transition‐metal‐catalyzed [4+3] Cycloaddition Reactionsmentioning
confidence: 99%
“…Very recently, Liu and co‐workers disclosed the highly diastereo‐and enantioselective gold‐catalyzed cyclization/[4+3] annulation cascade between 2‐(1‐alkynyl)‐2‐alken‐1‐ones 48 and anthranils 190 to yield epoxybenzoazepine products 191 (Scheme 49). [57] Treatment of species 191 a with Zn powder in DCM at room temperature led to an N−O bond cleavage to deliver benzoazepine derivative 192 in excellent yield without erosion of enantioselectivity.…”
Section: Transition‐metal‐catalyzed [4+3] Cycloaddition Reactionsmentioning
confidence: 99%
“…For example, Luo and co‐workers reported a Sc(OTf) 3 ‐catalysed [4+3]‐annulation reaction with cyclopropane 1,1‐diesters, [8a] which provided a practical and straightforward access to biologically important tetrahydro‐1‐benzazepines. In addition, various [3+4]‐cyclization reactions of anthranils with different substrates, such as γ ‐butyrolactone‐fused cyclopropanes, [8b] vinylcyclopropanes (VCPs), [8c] α ‐halo hydroxamates, [8d] and 2‐(1‐alkynyl)‐2‐alken‐1‐ones, [8e] have been established to access oxa‐bridged heterocycles. However, these approaches are restricted to build oxa‐bridged seven‐membered heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This strategy has been applied in various cascade cycloisomerization/[4 + n] cycloaddition reactions using different types of reaction partners. 8 For example, in 2019, Chi and co-workers disclosed the Au(I)/Nheterocyclic carbene (NHC) relay catalytic cycloisomerization/[4 + 2] cyclization reactions of enynamides with enals for the synthesis of furo [2,3-b]pyridine derivatives (Scheme 1A). 9 In 2020, Zhao et al elegantly demonstrated a highly stereoselective access to polyfunctionalized furan-fused ninemembered heterocycles by sequential Au(I) and Pd catalytic cycloisomerization/[4 + 5] annulation with vinyl ethylene carbonates (VECs).…”
Section: ■ Introductionmentioning
confidence: 99%